Some Remarks on Glass Seals from the Territory of Poland from the 17th-19th Centuries - Magdalena Bis (Fasciculi Archaeologiae Historicae, 2020)
This paper presents information about modern glass seals obtained during archaeological excavations carried out on the territory of modern-day Poland after 1987. The author reviews finds and their characteristics and based on such collected data attempts to indicate their quantitative diversity, territorial range, and chronology. The paper also focuses on markings identified on glass seals divided by their types. These are individualised signs, monograms, symbols, descriptive signs, and numerical signs, mostly trademarks. This analysis aims to outline the state of research and indicate various research questions associated with the production and use of stamped glass vessels in Poland, which require further studies.